The good, bad, and the ugly of regenerative therapies for erectile dysfunction - Campbell, Jeffrey D. (Transl Androl Urol, 2020)
Erectile dysfunction (ED) is a common condition which reduces quality of life of both patients and their partners, and is a significant health care expense every year. Although phosphodiesterase type-5 inhibitors are the current first-line treatment for men with ED, they are limited by their on-demand dosing, intolerance, and variable efficacy in complex patient populations such as men with multiple medical comorbidities or ED after pelvic surgery. Regenerative medicine has been introduced and investigated in andrology as an encouraging strategy to restore diseased erectile tissue structure and function. Novel regenerative therapies for ED are controversial but are perceived to offer a durable and safe tissue restorative approach to act as a long-term solution to this cumbersome disease process. Here, we review platelet-rich plasma, amniotic fluid membranes, low-intensity extracorporeal shockwave therapy, and stem cell therapy as regenerative strategies to treat ED. Most of these approaches have preclinical and occasionally clinical data to support their ongoing investigation; however, none of these treatments are currently supported for use in ED patients outside of clinical trials.